How Deep Time Can Help Shape the Present: Existential Economics, “Joyful Insignificance” and the Future of the Ecological Transition - Arnsperger, Christian (Text Matters: A Journal of Literature, Theory and Culture, 2022)
An awareness of deep time—both humanity’s deep past and the Earth’s deep future—and an understanding of its existential implications can significantly enhance the chances that humanity might still be able to transition towards an ecologically sustainable way of inhabiting the biosphere. This essay explains in detail why this is so, using analysis of a science fiction story that evokes existential horror at humanity’s ultimate cosmic insignificance. With the tools of “terror management theory” (a paradigm of existential thought based on the work of Ernest Becker and emphasizing the saliency of the denial of death in human motivation and behaviour) and of “existential economics” (an approach postulating that the way in which the economic system is organized and operates is crucially influenced by this widespread denial of death), the essay suggests that death denial has turned into the capitalist denial of life, and that only a deep reconciliation of humanity with its true ontological place in the universe will make it possible for us to transition towards a regenerative rather than a destructive system. This will entail new modes of human thinking, feeling, and acting anchored in a shared sense of “joyful insignificance,” as well as a renewed sense of “cosmic indigeneity”—a sense that all humans are indigenous to this planet and that this fact has major implications for how we ought to live into the deep future, anchored in our deep past.